The Concentration of 8-Hydroxy-2?-Deoxyguanosine in Plasma During the Menstrual Cycle in Young Japanese Women - Kaori Yama; Honoka Shinbo; Yuka Fujikane; Chiaki Mikami; Maiko Machida; Jun Miura (Mary Ann Liebert, 2022)
Background: The exact pathophysiology of premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) is still unknown. This study aimed to investigate the concentration of 8-hydroxy-2?-deoxyguanosine (8-OHdG) in plasma in relation to the menstrual cycle and the severity of premenstrual symptoms in young Japanese women. Methods: The study included 21 healthy Japanese women 19?24 years of age. Fourteen women had no or mild PMS [PMS (?)], while five women had moderate to severe PMS and two women exhibited PMDD [PMS (+)]. The concentration of 8-OHdG in plasma was measured by means of high-performance liquid chromatography?electrochemical detector. The Center for Epidemiologic Studies Depression (CES-D) scale was used to evaluate the depressive tendency. Results: The concentration of 8-OHdG before menstruation was significantly higher than that after menstruation in total subjects (p?=?0.04). In the PMS (+) group, the 8-OHdG concentration before menstruation was higher than that after menstruation (p?=?0.02). Moreover, the PMS (+) group showed a higher 8-OHdG concentration compared with the PMS (?) group before menstruation (p?<?0.01), as well as higher CES-D scores compared with the PMS (?) group both before and after menstruation (p?<?0.01). Conclusions: These results suggested that the oxidation of DNA occurred before menstruation in PMS. The depression was associated with PMS symptoms both before and after menstruation in patients with PMS. Oxidation of DNA due to oxidative stress and depression in PMS patients may be involved in the pathogenesis of PMS. Clinical Trial Registration number 15-02-011.